EFFECT OF WORK PLACE ENVIRONMENT ON EMPLOYEE RETENTION IN SELECTED SUPERMARKETS IN KENYA. - Muturu, Elizabeth Mumbi; Mose, Dr. Thomas (Human Resource and Leadership Journal, 2019)
Purpose: The purpose of the study was to establish the effect of work place environment on employees' retention in selected supermarkets in Kenya. The study specifically sought to determine the effects of job satisfaction, employee relations, employees occupational health and safety and working conditions on employees' retention in selected supermarkets in Kenya. Methodology: The study will adopt a descriptive research design. The study was undertaken in three selected supermarkets in Kenya notably; Tuskys supermarkets; Naivas supermarkets and Choppies supermarkets. The target population comprised of a total of 1500 staff working in the three selected supermarkets in Kenya. These included; 640 staff at Tuskys supermarkets 560 staff at Naivas supermarkets and 300 staff at Choppies supermarkets. The study adopted a stratified random sampling technique to select 316 respondents as the sample size for the study. Questionnaires were used as the main data collection instruments and a pilot study was conducted to pretest questionnaires for reliability. Descriptive statistics and multiple regression analysis were used to analyze the gathered data and the results were presented on tables, figures and graphs. Results: The study findings indicated that, job satisfaction, employee relations, employees' occupational health and safety and working conditions were the key effects of work place environment that affected employees' retention in selected supermarkets in Kenya. The study concluded that, commitment, employees' motivation and rewards are key aspects of employee job satisfaction which influences employee turnover rates in supermarkets. The study further concluded that job satisfaction the key factor that affects employee's retention most in supermarkets, followed by occupational health and safety, then working conditions with and lastly employee relations. Contribution to policy and practice: The study recommended that to improve on the level of employee job satisfaction, the supermarket management should offer the employee with good remuneration packages, recognize and reward the high performing employees. The supermarket management should adopt effective employee relations strategy through application of effective communication channel, use of effective conflict resolution methods, encouraging team building activities and providing better working conditions. The supermarket management should implement effective work safety procedures, increase the level of compliance with health and safety policies, implement effective work hazards and risks control methods and implement safety measures to avoid employee exposure to illness and accidents. The finally recommended that the supermarkets management should provide employees with favorable hours of work, provide flexible work schedule, increase on the employee work life balance and provide good work facilities.